Pengaruh Kondisi Kualiatas Air Terhadap Pertumbuhan Ikan Lele (Clarias sp.) - Darwis Triadi Telaumbanua; Ratna Dewi Zebua (CV. SINAR HOWUHOWU, 2026)
Water quality is one of the most important environmental factors affecting the growth and survival of catfish (Clarias sp.). A decline in water quality due to the accumulation of uneaten feed, fish feces, and organic matter can increase ammonia concentrations and reduce dissolved oxygen levels, thereby inhibiting fish growth. This study aimed to analyze the effect of polluted water conditions on the growth of catfish during a 30-day rearing period. The treatments consisted of clean water as the control (P1) and polluted water (P2). The observed parameters included absolute length gain, absolute weight gain, and survival rate (SR). The results showed that catfish reared in clean water exhibited better growth than those reared in polluted water. Fish in the control treatment achieved an average length gain of 4.2 cm and a weight gain of 28.5 g, while fish in polluted water showed a length gain of 3.1 cm and a weight gain of 21.4 g. The survival rate was also higher in the control treatment (96%) than in the polluted water treatment (90%). These findings indicate that poor water quality can inhibit the growth of catfish, although this species is still able to survive under suboptimal environmental conditions. Therefore, proper water quality management is essential to support optimal growth and improve the productivity of catfish culture.